INVESTMENT ANALYSIS FOR MATURE FIELD UNDER GROSS SPLIT PRODUCTION SHARING CONTRACT (The Indonesian Journal of Business Administration, 2019)
The Mature Field is an oil field which have experienced in declining its production and already in secondary recovery stage or in mature condition. The new infill drilling project is required to maintain the production level and prolong its economic of life. Therefore, investment analysis to investigate the economic feasibility of the identified opportunity for development of the field is required. This is important to The New Contractor in order to seek partners to operate the overall PSC contract including in Mature Field with using the Gross Split Scheme. Under Gross Split Scheme, The government is no longer burdened with cost recovery from the oil and gas development, while in Contractor side, the investment risk will be significantly different and impact to the economic feasibility and return of the investment as well.The environment analysis and capital budgeting techniques are performed to get the most optimum alternative and better perspective for investment decision in Mature Field. The environment analysis is based on data and information for the general oil and gas industry using Porter Five Forces Approach. While the investment analysis is based on capital budgeting technique which mainly to get the best economic feasibility parameter such as net present value, internal rate of return and profitability index including the sensitivity analysis.The investment analysis result shows that Gross Split PSC with project option provides better result to the Contractor at all economic parameters such as cashflow, NPV, profitability index and IRR. Sensitivity analysis is also performed to see how changes in the values of important variables affect the output / benefits.Considering IRR for the Gross Split PSC with Project is 18.74% which is above threshold of 15%. This investment in Mature Field is economically viable and competitive for many major oil companies to invest. Thus, The New Contractor should be able to seek Partner in order to operate Mature Field. Keywords: Capital Budgeting, Cost Recovery PSC, Gross Split PSC, Investment Analysis, Upstream Oil and Gas